2010
DOI: 10.1021/es102610x
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorinated Compounds in the Environment and the Blood of Residents Living near Fluorochemical Plants in Fuxin, China

Abstract: A fluorochemical industrial park was built in 2004 in Fuxin, China, for the production of polytetrafluoroethylene (PTFE) and perfluorobutane sulfonate (PFBS). Yet little is known about the distribution of fluorochemicals in the environment and in people living in and around the park. In this study, environmental samples were collected from 22 sites in Fuxin to investigate the extent of perfluorinated compound (PFC) contamination in the environment around the park, and in drinking water from the public water su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(96 citation statements)
references
References 36 publications
9
81
4
2
Order By: Relevance
“…In recent years, Fuxin City has been taking steps to develop the fluorochemical industry by establishing some fluorine chemical parks due to the local abundance of mineral fluorite (CaF 2 ), and it has become the main fluorochemical industry center in North China . Studies have reported the effect of PFAS emissions into the environment, which are absorbed by residents living near the parks (Bao et al 2011;Liu et al 2009;Wang et al 2013). Therefore, it is essential to further assess the seasonal variations, source emissions, and transporting behavior of PFASs in this area.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, Fuxin City has been taking steps to develop the fluorochemical industry by establishing some fluorine chemical parks due to the local abundance of mineral fluorite (CaF 2 ), and it has become the main fluorochemical industry center in North China . Studies have reported the effect of PFAS emissions into the environment, which are absorbed by residents living near the parks (Bao et al 2011;Liu et al 2009;Wang et al 2013). Therefore, it is essential to further assess the seasonal variations, source emissions, and transporting behavior of PFASs in this area.…”
Section: Study Areamentioning
confidence: 99%
“…PFBS was the dominant homologue of PFAS in samples from zone B and zone C. Bao et al (2011) reported that one of the industrial parks specializes in the manufacture of potassium perfluorobutane sulfonate (KPFBS) and fluoropolymers in zone B. Wang et al (2013) also found that KPFBS and perfluorobutanesulfonyl fluoride (PFBSF) are produced by electrochemical fluorination (ECF) process of the two parks.…”
Section: Seasonal Variation Of Pfass In Surface Water Of the Daling Rmentioning
confidence: 99%
See 2 more Smart Citations
“…The industrial production and use of PFASs resulted in high level detections in some hotspots. For example, the rivers upstream to the Liaodong (Fuxin City) (Bao et al, 2010) and Laizhou (Weifang City) Bays (Heydebreck et al, 2015), of which the direct release of ionic PFASs was suggested as the major source. The previous studies were mostly concentrated in the riverine and coastal region, and little is known in the open sea area.…”
Section: Introductionmentioning
confidence: 99%